2018
DOI: 10.1101/gr.225599.117
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes and DNA methylation shape meiotic DSB frequency in Arabidopsis thaliana transposons and gene regulatory regions

Abstract: Meiotic recombination initiates from DNA double-strand breaks (DSBs) generated by SPO11 topoisomerase-like complexes. Meiotic DSB frequency varies extensively along eukaryotic chromosomes, with hotspots controlled by chromatin and DNA sequence. To map meiotic DSBs throughout a plant genome, we purified and sequenced SPO11-1-oligonucleotides. SPO11-1-oligos are elevated in gene promoters, terminators, and introns, which is driven by AT-sequence richness that excludes nucleosomes and allows SPO11-1 access. A pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
367
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(400 citation statements)
references
References 113 publications
(204 reference statements)
33
367
0
Order By: Relevance
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…An important question raised by our study is why pericentromeric crossover frequency increases in the H3K9me2/non-CG pathway mutants reported here, but not in met1 and ddm1 where reduced pericentromeric crossover frequency is observed (Colomé-Tatché et al 2012;Melamed-Bessudo and Levy 2012;Mirouze et al 2012;Yelina et al 2012Yelina et al , 2015, despite both kyp suvh5 suvh6 and met1 showing increased SPO11-1-oligos in proximity to centromeres (Choi et al 2018). MET1 and DDM1 play major roles in the maintenance of DNA methylation in the CG context.…”
Section: Wwwgenomeorgmentioning
confidence: 98%
“…We propose that, while both CG and non-CG DNA methylation inhibit centromeric meiotic DSBs (Choi et al 2018), only non-CG methylation and/or H3K9me2 inhibit crossovers. In agreement with this idea, euchromatic crossover hotspots in A. thaliana can be silenced by RNA-directed DNA methylation associated with gain of H3K9me2 and both CG and non-CG methylation .…”
Section: Wwwgenomeorgmentioning
confidence: 99%
See 2 more Smart Citations